Autistic traits as predictors of post-traumatic stress symptoms among patients with borderline personality disorder - Carpita, Barbara; Bonelli, Chiara; Schifanella, Vincenzo; Nardi, Benedetta; Amatori, Giulia; Massimetti, Gabriele; Cremone, Ivan Mirko; Pini, Stefano; Dell’Osso, Liliana (Frontiers in Psychiatry, 2024)
Background: Autistic traits seem to be particularly frequent among patients with borderline personality disorder (BPD). Moreover, the autism spectrum is considered a vulnerability factor for the development of post-traumatic stress disorder (PTSD) symptoms, increasing the vulnerability of BPD subjects towards the development of a stress-related disorder.Aim: the study aimed to investigate the association between AT and trauma-related symptoms in a clinical sample of patients with BPD.Methods: 48 patients with a clinical diagnosis of BPD and 52 healthy control (HC) subjects were recruited and assessed with the Adult Autism Subthreshold Spectrum Self Report (AdAS Spectrum) questionnaire and the Trauma and Loss Spectrum -Self Report questionnaire (TALS -SR). The BPD group was divided into two subgroups: BPD with a symptomatological diagnosis of PTSD (pBPD=25) and BPD not diagnosed with PTSD (No-pBPD=23).The clinical sample scored significantly higher in almost all AdAS domains. Moreover, pBPD groups reported higher AdAS and TALS-SR scores in the total and in various domains than the No-pBPD group, which scored higher in several domains than HC. AdAS Restricted interests and rumination domain scores were positive predictors of BPD presence independently from PTSD, while Inflexibility and adherence to routine domain was a negative predictor.Finally, AdASHyper/hyporeactivity to sensory stimuli domain was a positive predictor only for inclusion in the pBPD group.Conclusion: our study confirmed the existence of a statistically significant relationship between the autism spectrum and BPD, while BPD subjects diagnosed with PTSD seem to show a higher autism spectrum burden.